KİL ÇEKİRDEKLİ DOLGU BARAJLARDA GERİLME VE DEFORMASYON ANALİZİ - KORKMAZ, MERAL (Fırat Üniveristesi, 2010)
Bu çalışmada merkezi kil çekirdekli kaya dolgu barajlarda inşa sonundaki gerilme ve deformasyonları incelenmiştir. Toplam gerilmelerin ve yer değiştirmelerin belirlenmesi amacıyla iki boyutlu düzlem şekil değiştirme prensibi kullanılarak, sonlu elemanlar metodu ile analizleri gerçekleştirilmiştir. Analizler Plaxis 8.x yazılımı yardımı ile incelenmiştir. Bu yazılım günümüzde pek yaygın olarak kullanılmakta ve rağbet görmektedir. Malzeme model parametreleri, önceki çalışmalar temelinde seçilmiştir. Daha sonra farklı malzeme değerleri ve farklı şev eğimleri seçilerek inşa sonu için analizler yapılmıştır. Yapılan analizlere ait gerilme ve deformasyon değerleri belirlenmiştir. Belirlenen değerlere ait grafikler çizilip, sonuçlar detaylı bir şekilde yorumlanmıştır.

In this study, the stresses and deformations at the end of construction were investigated for the central clay core rockfill and earthfill dams. The analyses were made using the principle of two-dimensional plane strain in order to determine total stresses and substitutions. The analyses were carried out using by Plaxis 8.x software based on finite element method. This software is widely used nowadays and the software has a considerable interest for engineers. Material model parameters were selected depending on previous studies. Then, the analyses were carried out for different materials and different slope gradients. The analyses were made for the situation at the end of the construction. The values of stresses and deformations were obtained using Plaxis 8.x software. The figures were plotted for obtained stresses and deformations and the results were interrupted in detail.
Stress and deformation analysis of clay core embankment dams
Keywords: İnşaat Mühendisliği